Corporate governance and corporate social responsibility (CSR) disclosure in an emerging economy: evidence from commercial banks of Kazakhstan. Issue 3 (3rd June 2019) - Orazalin, Nurlan
Abstract : Purpose: This paper aims to explore the extent and nature of corporate social responsibility (CSR) reporting practices in the banking sector of Kazakhstan and investigates the effects of board characteristics on CSR disclosures in the given emerging economy. Design/methodology/approach: Data on CSR disclosures were manually collected from annual reports of all commercial banks listed in the Kazakhstan Stock Exchange (KASE) for the period 2010-2016. Financial data were obtained from audited financial statements available on bank websites and the Web page of the National Bank of Kazakhstan. Findings: The empirical results reveal that board gender diversity has a positive influence on CSR reposting, while board size and board independence have no impact on the level of CSR disclosures. Furthermore, the results show that bank size and bank age are significant factors in the dissemination of CSR disclosures. Additionally, the findings suggest that banks with a share of foreign ownership disclose more extensive and transparent information on CSR activities than banks owned by local investors and state-owned banks. Originality/value: The study provides evidence on the relationship between corporate governance and the level of CSR in the context of an emerging economy such as Kazakhstan, representing the Central Asian region. The study contributes to the current literature by focusing on the banking sector of Kazakhstan as a research context due to its substantial representation in the capital market of the given emerging economy.